Prevalence of Clostridium spp., in Kashar cheese and efficiency of Lactiplantibacillus plantarum and Lactococcus lactis subsp. lactis mix as a biocontrol agents for Clostridium spp. - Demirbas, Fatmanur; Dertli, Enes; Arici, Muhammet (ELSEVIER, 2022)
Clostridium sporogenes and Clostridium tepidium strains were detected in traditional Kashar cheese samples with late blowing characteristics. To control Clostridium spp., in Kashar cheese, dairy originated Lactic Acid Bacteria (LAB) strains were tested under in vitro conditions and during Kashar production. Two strains, Lactiplantibacillus plantarum and Lactococcus lactis subsp. lactis demonstrated anticlostridial activity in vitro and the co-inoculum of these two strains (10(7) cfu g(-1)) were tested during the challenge test on Kashar cheese production in which a contamination ratio of 10(4) cfu g(-1) with spores of Cl. sporogenes were applied. Kashar samples were stored at 4 & DEG;C and 25 & DEG;C during 40 days of storage period and microbiological and physicochemical properties of Kashar samples were determined during this period. A decrement of nearly 1 log cfu g(-1) in Cl. sporogenes numbers was observed in Kashar samples produced with co-inoculum of Lb. plantarum and L. lactis subsp. lactis stored at 4 & DEG;C but this was not the case for the Kashar samples stored at 25 & DEG;C. This study revealed the potential of distinct LAB strains to control Cl. sporogenes spores in semi-hard cheese samples as biocontrol agents at 4 & DEG;C storage.
Keywords: Late blowing; Clostridium sporogenes; Biocontrol; Kashar cheese; Lactiplantibacillus plantarum; Lactococcus lactis subsp; Lactis; ACID BACTERIA; LISTERIA-MONOCYTOGENES; SPOROGENES; INHIBITION; TYROBUTYRICUM; SPORES; FERMENTATION; BEIJERINCKII; CULTURES; REUTERIN; Food Science & Technology